2021
DOI: 10.1021/acs.biochem.1c00168
|View full text |Cite
|
Sign up to set email alerts
|

The G132S Mutation Enhances the Resistance of Mycobacterium tuberculosis β-Lactamase against Sulbactam

Abstract: The current rise of antibiotic resistant forms of Mycobacterium tuberculosis is a global health threat that calls for new antibiotics. The β-lactamase BlaC of this pathogen prevents the use of β-lactam antibiotics, except in combination with a β-lactamase inhibitor. To understand if exposure to such inhibitors can easily result in resistance, a BlaC evolution experiment was performed, studying the evolutionary adaptability against the inhibitor sulbactam. Several amino acid substitutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 52 publications
1
17
0
Order By: Relevance
“…The most significant difference between BlaC and other class A β-lactamase active sites is the lack of Asn132 in the former, in which it is replaced by Gly. , Asn132 may help keep the 6α-1R-hydroxyethyl dihedral in Position II (Figure ), thereby lowering the barriers to reaction in carbapenemases. Previous structural and computational studies have suggested that interactions of Asn132 with the 6α-1R-hydroxyethyl group are important in determining carbapenemase activity. ,,, Comparisons between enzymes here (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The most significant difference between BlaC and other class A β-lactamase active sites is the lack of Asn132 in the former, in which it is replaced by Gly. , Asn132 may help keep the 6α-1R-hydroxyethyl dihedral in Position II (Figure ), thereby lowering the barriers to reaction in carbapenemases. Previous structural and computational studies have suggested that interactions of Asn132 with the 6α-1R-hydroxyethyl group are important in determining carbapenemase activity. ,,, Comparisons between enzymes here (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…36,37 A few laboratory evolution studies on BlaC found mutations in the second-shell residue 132, which is a conserved Asn in most class A β-lactamases, but not in BlaC. 10,17 Deep mutational scanning was performed on TEM-1, yielding the fitness effect of substitutions of every amino acid residue to all other 19 amino acids. 38,39 These extensive studies showed that robustness and evolvability of TEM-1 are dependent on the strength of purifying selective pressure, 38 and that mutational effects on protein thermodynamic stability shape the distribution of fitness effects of mutations.…”
Section: Discussionmentioning
confidence: 99%
“…New β-lactam resistant strains are frequently reported, with sometimes only one point mutation in the enzyme leading to a new catalytic function. [10][11][12][13] This room for evolution in β-lactamases is reflected in the low amino acid conservation. A sequence alignment of the β-lactamase from Mycobacterium tuberculosis (Mtb), BlaC, the object of this study, with 493 other class A β-lactamases shows 49%-81% identity.…”
mentioning
confidence: 99%
“…Residues are numbered according to Ambler notation, and correspond to residue numbers 43-307 of BlaC Uniprot entry P9WKD3-1, 29-291 of CTX-M-14 Uniprot entry Q9L5C7, 25-293 of KPC-2 Uniprot entry Q9F663, 28-292 of NMC-A Uniprot entry P52663, and 24-286 of TEM-1 Uniprot entry P62593. The purple shading indicates the degree of sequence identity.For in cell studies, these sequences are preceded by a TAT-signal sequence, for in vitro studies a N-terminal TEV cleavable HIS-tag was added[19]. The alignment is generated using Clustal Omega[40] and visualized using Jalview[46].…”
mentioning
confidence: 99%